A Legal Analysis of Online Prostitution: Challenges in Law Enforcement in the Digital Era (Open Society Conference, 2025)
The advancement of digital technology has transformed prostitution practices into online forms that are difficult to monitor and regulate legally. This article analyzes the existing positive legal framework in Indonesia concerning online prostitution and identifies the challenges in law enforcement in the digital era. The research employs a normative juridical approach with legislative and conceptual analyses. Findings indicate that current regulations such as the Electronic Information and Transactions Law (UU ITE), the Criminal Code (KUHP), the Pornography Law, and the Human Trafficking Law (UU TPPO) are not sufficiently effective in addressing online prostitution due to technical, juridical, institutional, and social obstacles. Law enforcement remains hindered by limited investigative capacity in digital forensics, inconsistent application of laws, and inadequate inter-agency coordination. This article proposes juridical solutions including regulatory reform that criminalizes the use of prostitution services, adoption of the Nordic legal model, enhancement of digital forensic technology, and improvement in law enforcement capacity and coordination. Educational approaches and restorative justice are also recommended to strengthen prevention efforts and protect sex workers. The study concludes that effective law enforcement against online prostitution requires a synergy of legal reform, technological advancement, and comprehensive social strategies.